The role of the Sarbanes-Oxley Act (SOX) in Reducing Agency Costs - Farhad Al-kake; Dler Mousa Ahmed (QALAAI ZANIST JOURNAL, 2019)
The purpose of this research is to explain the role of the Sarbanes-Oxley Act (SOX) in reducing agency costs in the companies operating in the Kurdistan Region of Iraq. In order to achieve the objectives of the study, a ten questions questionnaire has been designed and distributed to sixty-eight professional auditors operating in the region. This analysis is based on sixty-three of them. The researchers reached the main conclusion that the implementation of the Sarbanes-Oxley Act (SOX) has a significant role in reducing the costs of the agency in the companies operating in the region. The researchers also made a number of recommendations including the need to adopt the Sarbanes- SOX) in the Kurdistan Region of Iraq as the main tool for the control of companies.